Return of State Financial Losses on Corruption Crimes: Return of State Financial Losses on Corruption Crimes - Hidayatun Indriyani (Focus Journal : Law Review, 2022)
Corruption is an act of enriching oneself or prioritizing personal interests. Corruption can harm many parties, both society and the state. Corruption is a threat to the ideals of a just and prosperous society. Based on Law Number 31 of 1999 concerning Eradication of Criminal Acts of Corruption in conjunction with Law Number 20 of 2001, it is explained that the return of state funds or losses has been confirmed not to eliminate the conviction of perpetrators of corruption. Even though the perpetrator of the corruption crime has returned the state finances that he had corrupted before the court decision was handed down, the legal process is still ongoing because the crime has occurred. However, the return of corrupted state finances can be one of the factors that ease the sentence for the defendant when the judge makes a decision.